by sr_vineeth_ruveneco » Mon Aug 26, 2019 10:18 pm
Hi jfu.green,
Here is a step-by-step process in solving the equation:
y = 3x^2 - 5x - 7 Step 1: multiply both sides by 12
12y = 36x^2 - 60x - 84 Step 2: add 109 to both sides so that the term on the right can be factored
12y + 109 = 36x^2 -60x +25 Step 3: Factor the right side
12y + 109 = (6x - 5)^2 Step 4: square root both sides
sqrt (12y + 109) = 6x - 5 Step 5: add 5 to both sides
5 + sqrt (12y + 109) = 6x Step 6: divide both sides by 6
5 + sqrt (12y + 109) / 6 = x
Hope this helps!